STOCK EXCHANGE MARKETING AS A FACTOR IN THE DEVELOPMENT OF INFORMATION PROVISION OF PRICE FORMATION MANAGEMENT IN GOODS EXCHANGING - MOKLYAK, Myroslava; KUSTOV, Vitaliy (Herald of Khmelnytskyi National University. Economic sciences, 2022)
It was researched the economic nature of the concept of "exchange marketing" and the levels of its management of exchange activities in this article. We analyzed the specifics of the exchange marketing, that conditioned due to exchange services. It was proved that exchange marketing is a factor in the development of information management of pricing in goods exchanging. The foreign experience of using exchange marketing as a method of management of exchange activity and as a method of research the market of exchange services was studied. The definition of «information support for the management of exchange pricing of commodities» was formulated. The conceptual model of balanced development of information support of pricing management in goods exchange includes: first of all it includes the conceptual basis that consist: 1) methodology: methods (costly, marketing and parametrical) and approaches (organizational, local, system (complex), functional, marketing, processing and resulting); 2) principles: systematization, standardization, compatibility, data security, efficiency, reliability, adaptability, productivity, development, transparency and high standards of information disclosure; secondly, it includes tactical landmarks: 1) exchange system consolidation; 2) electronic securities and derivatives circulation streamlining; 3) the level of financial literacy awareness raising. It was proposed to use such a tool as Fillratio control to satisfy traders interests. It was turned out that the exchange gives the market makers a competitive advantage over traders by providing the last look system. It was determined that one of the goals of the exchange is to provide equal conditions for all market participants. It has been established if market makers given an opportunity to cancel any trader’s transaction, so they (market makers) will do that with the least market volatility and the least movement of the market price in a disadvantageous way for the market maker. It was substantiated that a large amount of turnover is occupied by algorithmic (automated) trading systems, the so-called trading robots of two types: arbitration and others among the investment-speculative operations.